Pengaruh Metode Pengolahan dan Suhu Penyangraian terhadap Karakter Fisiko-Kimia Kopi Robusta - Nanda Supriana; Usman Ahmad; Samsudin Samsudin; Eko Heri Purwanto (Pusat Penelitian dan Pengembangan Perkebunan, 2020)
The processing of coffee can be classified into 3 types namely: dry, semi-wet and wet processing. And then, roasting is the process of forming the taste and aroma of coffee. The study was conducted at Pakuwon Experimental Station, Coffee and Cacao Processing Units, and Integrated Laboratory of Balittri, and TTPHP Laboratory of IPB Bogor, from July until October 2019. The study aimed to investigate (1) the effect of processing methods on physical quality characters of green beans, and (2) the effect of processing methods and roasting temperatures on chemical characters of coffee roasted and organoleptic characters of coffee brewed. The completely randomized design in factorial 2 factors and 3 replications was used in this study. The first factor were 3 type of processing methods (dry, semi-wet, and wet), and the second factor were 2 level of roasting temperatures (180oC and 210oC). The variables observed in the green beans were physical quality characters, while in roasted coffee were water content, caffeine content, and antioxidant activity, and in brewed coffee were organoleptic characters. Result showed that the best green beans was produced from a wet processing method with a minimum total defect value of 21.33 (quality 2). Roasting temperature has a very significant effect (p<0.01) on water content and antioxidant activity, while caffeine content is not significantly affected. Based on the results of cupping test, the best brewed coffee (final score >80.00) was obtained from the treatments of a dry, semi-wet and wet processing method with a roasting temperature of 210°C.